The Determinant Factor of the Principal Leadership Solutions in Facing the 21st-Century Learning - Muhammad Saifurrahman; Putu Sudira; Rihab Wit Daryono (Universitas Pendidikan Ganesha, 2021)
Principal leadership is very important in the education and learning efforts of the 21st-century. This study aims to find determinants of principal leadership solutions in dealing with 21st-century learning in Vocational High Schools (VHS). This research was conducted with a total sample of 64 respondents from the principals, the vice principal for field I-IV, the head of department, and staff. The data analysis used the Exploratory Factor Analysis (EFA) method to test the validity of the constructs and to estimate the reliability of the data. Furthermore, the t-test, One Way Anova, and Games-Howell test were used to test the difference in the average rating based on the characteristics of the respondent's dimensions. The results of the EFA analysis show that seven sub-variables are consisting of 29 determinants of the principal's leadership solution which are identified at 74.266%. The results of the instrument reliability estimation have a reliable level. Based on the different tests using the t-test on the gender dimension and the One Way Anova test on the last position and education dimension, it was concluded that there was no significant difference in the assessment of respondents. The Games-Howell test post-hoc revealed that there were significant differences based on the 29-33 year age dimension and the 5-9-year-old teaching experience dimension.